Molecular Diagnosis and Prenatal Phenotype Analysis of Eight Fetuses With Ciliopathies - Liu, Yuefang; Wang, Hui; Jin, Xin; Shao, Qixiang; Pan, Qiong (Frontiers in Genetics, 2021)
Human ciliopathies are hereditary conditions caused by variants in ciliary-associated genes. Ciliopathies are often characterized by multiple system defects. However, it is not easy to make a definite diagnosis in the prenatal period only based on the imageology. In this report, eight new prenatal cases from five unrelated families diagnosed with ciliopathies were systematically examined. The clinical manifestations of these fetuses showed such prenatal diagnostic features as occipital encephalocele, polydactyly and polycystic kidneys. Situs inversus caused by CPLANE1 variant was firstly reported. In family 1 and 3, homozygous variants of CPLANE1 and NPHP4 caused by consanguineous marriage and uniparental disomy were detected by whole- exome sequencing, respectively. In family 2, 4 and 5, compound heterozygotes of TMEM67 and DYNC2H1 including two novel missense variants and one novel nonsense variant were identified. The distribution of pathogenic missense variants along TMEM67 gene mainly clustered in the extracellular cysteine rich region, extracellular area with unknown structure, and the transmembrane regions. Genotype-phenotype relationship between CPLANE1 and TMEM67 genes was concluded. This report describes new clinical manifestations and novel variants in CPLANE1, TMEM67, NPHP4 and DYNC2H1.